Prevention of Cardiac Surgery–Associated Acute Kidney Injury by Implementing the KDIGO Guidelines in High-Risk Patients Identified by Biomarkers: The PrevAKI-Multicenter Randomized Controlled Trial. (8th May 2021) - Zarbock, Alexander; Küllmar, Mira; Ostermann, Marlies; Lucchese, Gianluca; Baig, Kamran; Cennamo, Armando; Rajani, Ronak; McCorkell, Stuart; Arndt, Christian; Wulf, Hinnerk; Irqsusi, Marc; Monaco, Fabrizio; et al.
Abstract : BACKGROUND: Prospective, single-center trials have shown that the implementation of the Kidney Disease: Improving Global Outcomes (KDIGO) recommendations in high-risk patients significantly reduced the development of acute kidney injury (AKI) after surgery. We sought to evaluate the feasibility of implementing a bundle of supportive measures based on the KDIGO guideline in high-risk patients undergoing cardiac surgery in a multicenter setting in preparation for a large definitive trial. METHODS: In this multicenter, multinational, randomized controlled trial, we examined the adherence to the KDIGO bundle consisting of optimization of volume status and hemodynamics, functional hemodynamic monitoring, avoidance of nephrotoxic drugs, and prevention of hyperglycemia in high-risk patients identified by the urinary biomarkers tissue inhibitor of metalloproteinases-2 [TIMP-2] and insulin growth factor–binding protein 7 [IGFBP7] after cardiac surgery. The primary end point was the adherence to the bundle protocol and was evaluated by the percentage of compliant patients with a 95% confidence interval (CI) according to Clopper-Pearson. Secondary end points included the development and severity of AKI. RESULTS: In total, 278 patients were included in the final analysis. In the intervention group, 65.4% of patients received the complete bundle as compared to 4.2% in the control group (absolute risk reduction [ARR] 61.2 [95% CI, 52.6-69.9]; P < .001). AKI rates were statistically not different in both groups (46.3% intervention versus 41.5% control group; ARR −4.8% [95% CI, −16.4 to 6.9]; P = .423). However, the occurrence of moderate and severe AKI was significantly lower in the intervention group as compared to the control group (14.0% vs 23.9%; ARR 10.0% [95% CI, 0.9-19.1]; P = .034). There were no significant effects on other specified secondary outcomes. CONCLUSIONS: Implementation of a KDIGO-derived treatment bundle is feasible in a multinational setting. Furthermore, moderate to severe AKI was significantly reduced in the intervention group.